1999
DOI: 10.1002/etc.5620180824
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of linear alkylbenzene sulfonate in soil columns

Abstract: Abstract-This study investigated the ability of a microbial community to degrade linear alkylbenzene sulfonate (LAS) in soil columns under water-saturated conditions. The microbial mineralization of LAS was further studied in a batch experiment using pre-exposed and unexposed soil as well as soil from the inlet and outlet of the columns. The LAS (4 mg/L) was added continuously to the columns. Three pulses of 14 C-labeled LAS ( 14 C-dodecyl-[6]-benzene sulfonate) were added at intervals of 2 weeks, and the mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 19 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…It was also determined that the biodegradation of LAS was faster under fully oxygenated laboratory conditions than that of in the field [24]. The primary degradation of LAS in soil columns under water-saturated conditions was close to 100% while mineralization only occurred up to 9% [59].…”
Section: Biodegradation Of Linear Alkylbenzene Sulfonate (Las)mentioning
confidence: 96%
“…It was also determined that the biodegradation of LAS was faster under fully oxygenated laboratory conditions than that of in the field [24]. The primary degradation of LAS in soil columns under water-saturated conditions was close to 100% while mineralization only occurred up to 9% [59].…”
Section: Biodegradation Of Linear Alkylbenzene Sulfonate (Las)mentioning
confidence: 96%
“…The rate o f surfactant degradation was enhanced by adding nutrients, such as nitrogen, phosphorus, and oxygen. Branner et al (1999) studied the degradation o f LAS in soil columns under water-saturated conditions. It was found that primary degradation was close to 100% while mineralization only occurred up to 9%.…”
Section: Biodégradation Of Alkylphenol Ethoxylates (Apeos)mentioning
confidence: 99%